A taxonomic revision of Antillean Symplocos (Symplocaceae) - Fritsch, Peter W; Al, Frank (Phytotaxa, 2015)
We present a taxonomic revision of Symplocos (Symplocaceae, Ericales, Angiospermae) for the Antilles. The seventeen species recognized are distributed among three major clades of the genus corresponding to S. sect. Hopea, S. ser. Symplocos, and S. ser. Urbaniocharis, the latter two comprising S. sect. Symplocos. Fifteen of the species are endemic to the Antilles and only one (S. cubensis) occurs in more than one major island group. The revision includes keys, descriptions, distribution maps, and a conservation assessment for each species. Symplocos baracoensis is described as new, and lectotypes are designated for S. apiculata, S. domingensis, S. guadeloupensis, S. harrisii, S. hyboneura, S. jamaicensis, S. jurgensenii, S. lanata, S. latifolia, S. micrantha, S. pilifera, S. polyantha, S. tubulifera, and S. urbaniana.